2004
DOI: 10.1149/1.1760576
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystalline ZnFe[sub 2]O[sub 4] and Ag-Doped ZnFe[sub 2]O[sub 4] Films Used as New Anode Materials for Li-Ion Batteries

Abstract: Nanocrystalline ZnFe 2 O 4 and Ag x ZnFe 2 O 4 (x ϭ 0.16, 0.37, 0.50) thin films have been prepared by reactive pulsed laser deposition, and used as anode materials for Li-ion batteries for the first time. X-ray diffraction ͑XRD͒ and scanning electron microscopy measurements showed that the prepared films were composed of a nanocrystalline structure with the average particle size less than 100 nm. The initial reversible capacity of ZnFe 2 O 4 and Ag 0.37 ZnFe 2 O 4 film electrodes reached 556 and 700 mAh/g, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
90
0
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(106 citation statements)
references
References 19 publications
(20 reference statements)
5
90
0
6
Order By: Relevance
“…The first irreversible capacity can be attributed to the decomposition of electrolyte to form the solid electrolyte interphase (SEI) on the electrode surface. 34,40,60 As for many other conversion materials, the discharge curve spans over a wide potential range, in this case 3V, with a medium de-lithiation potential of 1.7 V vs. Li/Li + (at 1C), affecting the available energy content in a full cell. In addition, there is a large hysteresis, which will affect the energy efficiency.…”
Section: Electrochemical Lithiation and De-lithiation Of Znfe 2 O mentioning
confidence: 99%
See 1 more Smart Citation
“…The first irreversible capacity can be attributed to the decomposition of electrolyte to form the solid electrolyte interphase (SEI) on the electrode surface. 34,40,60 As for many other conversion materials, the discharge curve spans over a wide potential range, in this case 3V, with a medium de-lithiation potential of 1.7 V vs. Li/Li + (at 1C), affecting the available energy content in a full cell. In addition, there is a large hysteresis, which will affect the energy efficiency.…”
Section: Electrochemical Lithiation and De-lithiation Of Znfe 2 O mentioning
confidence: 99%
“…This material demonstrated a rather poor cycling performance since only a capacity retention of 78% was obtained after 100 cycles. 34 Deng et al • Simple synthesis route (easy to operate) conc. HNO 3 ;…”
Section: Introductionmentioning
confidence: 99%
“…Pulsed laser deposition techniques [7][8][9], dip coating [10], sputtering [11], laser ablation [12], vacuum arc evaporation [13] and the sol-gel method [14] have been used to synthesis mixed iron-oxide thin films. To obtain crystallization, these techniques require heating the substrate for several hundred degrees Celsius.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it was found that NiCo 2 O 4 can be cycled vs. both Li and Na [2], while XAS studies revealed the full reduction to the metallic state and an incomplete oxidation during charge [3]. Other examples of spinel materials studied so far contain iron in their stoichiometry, such as NiFe 2 O 4 [4] ZnFe 2 O 4 [5], and CoFe 2 O 4 [6] and CuFe 2 O 4 [7].…”
Section: Introductionmentioning
confidence: 99%
“…Powerful spectroscopic techniques have been used to gain for information about the reactions taking place. Thus Mössbauer spectroscopy (MS) [4], XPS [5,8] and XAS [3] were used for these purposes. In this communication, we show that 57 Fe MS provides valuable information about the changes in oxidation state, local environment and magnetic ordering of CoFe 2 O 4 in electrodes cycled vs. lithium.…”
Section: Introductionmentioning
confidence: 99%